Tree Vegetation Analysis after 10 Years of Mount Merapi Eruption - Utami, Inggita; Yusuf, Febriant Isabella; Husna, Fahmiatul (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The 2010 Mount Merapi eruption caused variety of damage level in Mount Merapi National Park (MMNP). Over time, composition of vegetation and carbon stocks continues to change towards a climax. The objective of this study is to analyze the vegetation composition and tree carbon stocks in MMNP forest land with variations of damage level forest land after 10 years of Mount Merapi eruption in 2010. Data collection was administered from December 2019 to January 2020 in Dlimas (heavy damage), Gandog (moderate damage) and Tritis (minor damage). Plot placement was determined randomly in each location by making the main plot of 20 x 100 m for large trees and a subplot of 5 x 40 m for small trees (poles, saplings, seedlings). The composition vegetation analysis was performed using an inverted J curve, Importance Value (IV) index and Shannon-Wiener Diversity Index (H'). The calculation of carbon stock and woody necromass (dead trees) using allometric equations. Based on the results of data analysis, there are 40 species from 34 families. Moderate damage location has the highest diversity index H’ for large trees of 0.45 and small trees of 2.23. The highest carbon stock of tree stands and woody necromass was in minor damage of 172.06 ton ha-1, followed by moderate damage of 119.42 ton ha-1 and minor damage as much as 10.29 ton ha-1. Moderate and minor damage locations have curves that are close to inverted J shape with the density of seedlings and saplings more than large trees as a form of secondary forest regeneration. Abiotics correlated to carbon stock and tree density consist of air temperature, air humidity, soil pH, soil moisture, land slope and elevation. Ten years after the eruption, forests with moderate dan minor damage in MMNP Yogyakarta Province have high regeneration rate and carbon stock.